Elastohydrodynamics lubrication for bio-based lubricants in elliptical conjuction [electronic resource] - Nazri Huzaimi Zakaria, 1984-; Fakulti Kejuruteraan Mekanikal (2010)
Thesis (Sarjana Kejuruteraan (Mekanikal)) - Universiti Teknologi Malaysia, 2010